2020
DOI: 10.1093/ajcp/aqaa228
|View full text |Cite
|
Sign up to set email alerts
|

Variable Performance in 6 Commercial SARS-CoV-2 Antibody Assays May Affect Convalescent Plasma and Seroprevalence Screening

Abstract: Objectives Serologic detection of prior severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is needed for definition of convalescent plasma donors, for confounding SARS-CoV-2 presentation, and for seroprevalence studies. Reliable serologic assays with independent validation are required. Methods Six SARS-CoV-2 antibody assays from Beckman Coulter, Euroimmun (IgG, IgA), Roche, and Siemens (Centaur, Vista) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
26
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 20 publications
10
26
2
Order By: Relevance
“…Considering the cut-offs suggested by the manufacturer (i.e., 1.0 AU/mL for IgM and 1.1 AU/mL for IgG), the immunoglobulin rise could be considered significant seven days after fever onset. These findings are in agreement with those reported by us [2] and other Authors [6,16,17]. In addition, Kowitdamrong et al showed that seroconversion is fast in patients with Mod/Sev disease than in mild disease [16].…”
Section: Time Kinetics Of Igm and Iggsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering the cut-offs suggested by the manufacturer (i.e., 1.0 AU/mL for IgM and 1.1 AU/mL for IgG), the immunoglobulin rise could be considered significant seven days after fever onset. These findings are in agreement with those reported by us [2] and other Authors [6,16,17]. In addition, Kowitdamrong et al showed that seroconversion is fast in patients with Mod/Sev disease than in mild disease [16].…”
Section: Time Kinetics Of Igm and Iggsupporting
confidence: 93%
“…Second, COVID-19 convalescent plasma is one of the available treatment option and it is necessary to characterize the antibody response of each individual before accepting her/his for plasma donation [5]. Third, to assist in the diagnosis of patients who present later in their disease course or when the standard RNA detection methods are negative but clinical suspicion is high and other diseases have been ruled out [6,7]. Fourth, for epidemiological studies to determine seroprevalence in a population of high-risk subgroups of the population (e.g.…”
mentioning
confidence: 99%
“…These results are expressed as extinction coefficient (signal/cutoff) ratios and are interpreted as positive (≥ 1.00), equivocal (> 0.80 to < 1.00), or non-reactive (≤ 0.80) 11 . Reactive results are confirmed by the Siemens SARS-CoV-2 Total Ig Assay, which detects both IgM and IgG antibodies against RBD of the S1 subunit of the Spike protein 12 . For analysis, reactive results were defined as positive, and equivocal or non-reactive results were defined as negative.…”
mentioning
confidence: 84%
“…Among vaccine non-responders however, patients with CLL had significantly lower extinction coefficient ratios compared to those without CLL (median ratio 0.02 (range 0.02 – 0.06) versus 0.15 (range 0.02 – 0.91), respectively, p < 0.001) ( Figure 1B ). It should be noted that values below 0.10 are suggestive of no antibody response, whereas values closer 1.00 may suggest evolving or declining responses 12 .…”
mentioning
confidence: 99%
“…In the course of the recent months, various studies have assessed the diagnostic performance characteristics of SARS-CoV-2-specific serological assays, indicating imperfect sensitivity and specificity of the assays, with higher reliability of assays targeting IgG compared to IgM- and IgA-specific ones [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Specificity problems with serological assays based on whole viral antigens [ 15 ] facilitated the development of more specific assays based on chosen structures of the virus only.…”
Section: Introductionmentioning
confidence: 99%